2005
DOI: 10.1007/s00428-005-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hypermethylation of RASSF1A promoter in ovarian borderline tumors and carcinomas

Abstract: The newly identified 3p21.3 tumor suppressor gene RASSF1A is inactivated by hypermethylation in variable solid tumors, including those of the lung, breast, prostate, kidney, and ovary. The purpose of this study was to evaluate the methylation status of RASSF1A in various types and stages of ovarian epithelial tumors. We analyzed the DNA methylation status of ovarian tumors using methylation-specific polymerase chain reaction in 54 frozen ovarian tumor tissues and in 97 cases of archival ovarian serous epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…RASSF1 (Makarla et al 2005, Choi et al 2006, Bol et al 2010, APC (Rathi et al 2002, Makarla et al 2005, CDH13 (Makarla et al 2005, Bol et al 2010, CDH1 (Rathi et al 2002) and GSTP1 (Makarla et al 2005, Bol et al 2010, which showed an increased methylation frequency in FTC compared with control tissue in this study, have previously been reported in ovarian cancer and not in its precursors. Choi et al (2006) showed that RASSF1 was frequently methylated in borderline tumours and ovarian carcinoma and showed a significant correlation with the presence of peritoneal implants, micro-invasion and bilaterality. Interestingly, four genes that were only found in invasive ovarian cancer and not in non-invasive lesions or normal tissue, RASSF1, APC, MGMT and GSTP1 (Makarla et al 2005), showed exactly the same pattern in this study.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…RASSF1 (Makarla et al 2005, Choi et al 2006, Bol et al 2010, APC (Rathi et al 2002, Makarla et al 2005, CDH13 (Makarla et al 2005, Bol et al 2010, CDH1 (Rathi et al 2002) and GSTP1 (Makarla et al 2005, Bol et al 2010, which showed an increased methylation frequency in FTC compared with control tissue in this study, have previously been reported in ovarian cancer and not in its precursors. Choi et al (2006) showed that RASSF1 was frequently methylated in borderline tumours and ovarian carcinoma and showed a significant correlation with the presence of peritoneal implants, micro-invasion and bilaterality. Interestingly, four genes that were only found in invasive ovarian cancer and not in non-invasive lesions or normal tissue, RASSF1, APC, MGMT and GSTP1 (Makarla et al 2005), showed exactly the same pattern in this study.…”
Section: Discussionsupporting
confidence: 48%
“…For ovarian cancer, methylation has been shown in a number of tumour suppressor genes such as RASSF1, APC, PTEN, BRCA1, RARb, CDH13 and HIC1 (Rathi et al 2002, Makarla et al 2005, Choi et al 2006, Tam et al 2007. For FTC and its precursors, methylation has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of the RASSF1A promoter is described as an early and frequent event in tumorigenesis, thus RASSF1A can serve as a useful diagnostic marker in cancer screening (Dammann et al, 2000;Dammann et al, 2001;Liu WJ et al, 2013), including ovarian cancer (Agathanggelous et al, 2001;Yoon et al, 2001;Rathi et al, 2002;Ibanez et al, 2004;Makarla et al, 2005;Choi et al, 2006;Ma et al, 2009;BonDurant et al, 2011;Bhagat et al, 2012).…”
Section: Aberrant Methylation Of Rassf2a In Tumors and Plasma Of Patimentioning
confidence: 99%
“…In this study, the doubling time of PTX-resistant cell lines was set as 36 to 48 h. So, treatment of 5-aza-dc should last for at least 96 h to fully exert its demethylation effect. According to some studies, the application of 5-aza-dc can restore the expression of hMLHI gene that is silenced by methylation, thus reversing the development of resistance of tumor cells to chemotherapeutics [12][13][14][15][16][17][18]. Staub et al [11] in a study on HSulf-I in ovarian cancer, found that abnormal expression of HSulf-I can induce a decrease in cytotoxicity caused by cobalt drugs, which might be due to the downregulation caused by abnormal methylation in promotor, while the drug resistance can be reversed after the treatment with methyltransferase inhibitor.…”
Section: Discussionmentioning
confidence: 99%